Максим Рильський як науковий наставник повоєнного покоління народознавців України - Зінич, В. (Народна творчість та етнографія, 2005)
In 1945 compare to pre-war times Ukraine had a very few ethnographers. It is connected not as much to their death during the war as to the repressions of the 1930th. Most of the folklorists and especially ethnographers were accused in being nationalists; they were repressed and physically destroyed. After the Second World War situation changed a little bit for the best. A big role in it played M. Rylsky. Thanks to his hard work at the beginning of the 1950th the folk studies in Ukraine got a second life. This article gives readers a history of the division of Ethnography at Rylsky Institute. The author of the article is one of the post-war graduate students of this department and his memoirs give a taste of the Institute's life in 1950th and M. Rylsky's role in the formation of the young scholars' scientific interests. M. Rylsky was a scientific guardian of the author's candidate dissertation and he had a chance to direct a young scholar into more ethnographical branch. V. Zinych also describes personality of M. Rylsky, his kindness toward people surrounding him.